Protein kinase D plays a crucial role in maintaining cardiac homeostasis by regulating post-translational modifications of myofilament proteins - Herwig, Melissa; Begovic, Merima; Budde, Heidi; Delalat, Simin; Zhazykbayeva, Saltanat; Sieme, Marcel; Schneider, Luca; Jaquet, Kornelia; Mügge, Andreas; Akın, Ibrahim; El-Battrawy, Ibrahim; Fielitz, Jens; et al. (International journal of molecular sciences, 2024)
Protein kinase D (PKD) enzymes play important roles in regulating myocardial contraction, hypertrophy, and remodeling. One of the proteins phosphorylated by PKD is titin, which is involved in myofilament function. In this study, we aimed to investigate the role of PKD in cardiomyocyte function under conditions of oxidative stress. To do this, we used mice with a cardiomyocyte-specific knock-out of Prkd1, which encodes PKD1 (Prkd1loxP/loxP; αMHC-Cre; PKD1 cKO), as well as wild type littermate controls (Prkd1loxP/loxP; WT). We isolated permeabilized cardiomyocytes from PKD1 cKO mice and found that they exhibited increased passive stiffness (Fpassive), which was associated with increased oxidation of titin, but showed no change in titin ubiquitination. Additionally, the PKD1 cKO mice showed increased myofilament calcium (Ca2+) sensitivity (pCa50) and reduced maximum Ca2+-activated tension. These changes were accompanied by increased oxidation and reduced phosphorylation of the small myofilament protein cardiac myosin binding protein C (cMyBPC), as well as altered phosphorylation levels at different phosphosites in troponin I (TnI). The increased Fpassive and pCa50, and the reduced maximum Ca2+-activated tension were reversed when we treated the isolated permeabilized cardiomyocytes with reduced glutathione (GSH). This indicated that myofilament protein oxidation contributes to cardiomyocyte dysfunction. Furthermore, the PKD1 cKO mice exhibited increased oxidative stress and increased expression of pro-inflammatory markers interleukin (IL)-6, IL-18, and tumor necrosis factor alpha (TNF-α). Both oxidative stress and inflammation contributed to an increase in microtubule-associated protein 1 light chain 3 (LC3)-II levels and heat shock response by inhibiting the mammalian target of rapamycin (mTOR) in the PKD1 cKO mouse myocytes. These findings revealed a previously unknown role for PKD1 in regulating diastolic passive properties, myofilament Ca2+ sensitivity, and maximum Ca2+-activated tension under conditions of oxidative stress. Finally, we emphasized the importance of PKD1 in maintaining the balance of oxidative stress and inflammation in the context of autophagy, as well as cardiomyocyte function.